Warm-keeping and health-care composite fabric and preparation method thereof

By composite weaving of modified polypropylene fiber with modified polyester hollow fiber, and using the blend spinning technology of modified tourmaline powder and seagull stone powder, the shortcomings of warm polyester fabrics in the prior art are solved in the prior art in terms of warm and health care, and composite fabrics with efficient warm and multifunctional health care effects are achieved.

CN119777051AActive Publication Date: 2025-04-08NANTONG XUANMI TEXTILE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411779951.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-08
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In the prior art, thermal polyester fabrics have shortcomings in warm and health care, and it is difficult to achieve efficient thermal and multifunctional health care effects at the same time.

Method used

Modified polypropylene fiber is combined with modified polyester hollow fiber, mixed aerogel is prepared by vapor phase silica and graphene oxide, and combined with acrylic trichlorosilane, modified tourmaline powder and seagull stone powder are blended to form a composite fabric with warm, antibacterial and health care effects.

Benefits of technology

It achieves the efficient warm-keeping effect of the fabric. At the same time, it promotes blood circulation, improves immune function, and achieves multifunctional health care effects through the infrared radiation and negative ions of modified tourmaline powder.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a warm-keeping and health-care composite fabric and a preparation method thereof, and relates to the technical field of functional fabrics. The preparation method comprises the following steps: firstly, combining fumed silica with graphene oxide hydrogel to prepare mixed aerogel; the mixed aerogel is combined with allyl trichlorosilane, and is grafted to a macromolecular chain of polypropylene through maleic anhydride, so that the compatibility is improved, and the agglomeration problem is solved; secondly, calcining tourmaline, then directly carrying out quenching hydration modification, combining Si-OH groups on the surface with active groups in a polyester molecular chain, and spinning into hollow fibers; the mixed aerogel can absorb far infrared rays dissipated and emitted by the modified tourmaline, and the aerogel absorbing the far infrared rays can generate a resonance effect and a warm effect and permeate into the deep layer of the skin; the modified tourmaline has the capability of generating negative ions, and the gull rock powder is added for combined action, so that the antibacterial effect is achieved by destroying the structure of bacteria, and the health-care effect is achieved. The composite fabric prepared by the invention has warm-keeping and health-care effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional fabrics, in particular to a thermal insulation and health-care composite fabric and a preparation method thereof. Background Art

[0002] As people's material and cultural level improves, their requirements for fabrics are also increasing. They not only require warmth and beauty, but also pay more attention to comfort and functionality. Functional textiles have become one of the future development trends of the textile industry, and will form the general trend of future textiles together with fine-denier fiber textiles, non-woven fabrics, composite materials, and environmentally friendly materials. Researching and producing functional fabric products that are beneficial to human ecology and health has become a trend in the world today.

[0003] Tourmaline powder is a powder obtained by mechanically crushing tourmaline ore after removing impurities. Tourmaline powder is used in the textile industry to make environmentally friendly carbon cloth. Ultrafine tourmaline powder is made into ultrafine fibers, which can be made into anti-magnetic, moisture-proof, warm quilts, cotton pads, anti-electromagnetic radiation shirts, vests, insoles, etc. It can also be used in bedrock baths, steam rooms, light wave rooms, sauna facilities and environmentally friendly home decoration. At present, the application of tourmaline powder in the research and development of warm polyester fabrics is a direction with development and application prospects. Summary of the invention

[0004] The object of the present invention is to provide a thermal insulation and health care composite fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermal insulation and health care composite fabric, wherein the fabric is compositely woven with modified polypropylene fiber and modified polyester hollow fiber.

[0006] Furthermore, the modified polypropylene fiber is prepared by preparing a mixed aerogel of fumed silica and graphene, which is then combined with acryltrichlorosilane and spun by grafting maleic anhydride into polypropylene.

[0007] Furthermore, the modified polyester hollow fiber is prepared by spinning a blend of modified tourmaline powder, gull stone powder and polyester.

[0008] Furthermore, a method for preparing a thermal insulation and health care composite fabric comprises the following preparation steps:

[0009] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1-5:1, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in vacuum for 24 h, the vacuum degree being -0.085 MPa, to prepare a mixed aerogel;

[0010] (2) 8-9.6 parts of polypropylene, 0.5-1.5 parts of allyltrichlorosilane, 0.5-1.5 parts of maleic anhydride, 0.001-0.002 parts of catalyst, and 0.4-1.8 parts of mixed aerogel are placed in a high-speed stirrer, first stirred at a low speed of 60-120 rpm for 5-15 minutes, then stirred at a high speed of 400-800 rpm for 15-25 minutes, and the stirring temperature is controlled to be always at 100° C. to make various raw materials evenly mixed, and then placed in a reactive twin-screw extruder for screw extrusion. The temperature is 200-230°C, after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles are put into a spinning screw extruder, and the molten material enters a spinneret with 24 holes through a spinneret assembly to be extruded into melt fibers, and then cooled by cooling wind with a wind temperature of 30°C, and then stretched by a hot roller at 50-90°C, with a stretching multiple of 1.5-3.0, and finally wound on a winder with a winding speed of 1500-3000m / min to obtain modified polypropylene fibers;

[0011] (3) placing the tourmaline powder in a methane fluorine furnace, heating it to 500-700° C., and continuing to calcine for more than 4 hours; quickly placing the calcined tourmaline powder in a magnesium hydroxide aqueous solution with a pH of 10-11 and a solid-to-liquid ratio of 1:5-20, soaking for 1-3 hours, then filtering out the solid, repeatedly washing with water until the filtrate is acid-base neutral, filtration, and aging for 12-24 hours, and then drying in a 60° C. oven until the moisture content is less than 10%, thereby obtaining modified tourmaline powder;

[0012] (4) 6-9 parts of conventional polyester chips, 0.5-1.5 parts of modified tourmaline powder, 0.5-1 parts of 20 nm seagull stone powder, and 0.2-0.7 parts of ethyl acetate are put into a high-speed stirrer, stirred at a speed of 500 rpm for 30 minutes, and the stirring temperature is controlled to be always at 220° C. to make various raw materials evenly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature is 250-270° C., after melt mixing, extrusion, drawing, and pelletizing to obtain polyester masterbatch; conventional polyester chips and polyester masterbatch are blended, melt-spun at a spinning temperature of 290° C. and a spinning speed of 2600 m / min, and a "C" type microporous spinneret is used to obtain modified polyester hollow fibers; modified polypropylene fibers and modified polyester hollow fibers are mixed and woven at a mass ratio of 1:0.5-2 to prepare composite fabrics.

[0013] Furthermore, the quick freezing temperature in step (1) is -40°C.

[0014] Furthermore, in step (2), the catalyst is benzoyl peroxide.

[0015] Furthermore, in step (2), the screw extrusion temperature is 190-250°C.

[0016] Furthermore, the heating rate in step (3) is 5-10°C / min.

[0017] Furthermore, in step (4), the mass ratio of conventional polyester chips to polyester masterbatch is 1:1.

[0018] Furthermore, in step (4), the fabric weight is 150-200 g / m 2 .

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention uses mixed aerogel modified polypropylene fiber, modified tourmaline, seagull stone powder modified polyester hollow fiber, and composite weaving into fabric to achieve the effects of warmth preservation and health care.

[0021] First, fumed silica has stronger surface activity than ordinary silica, is rich in silanol and siloxane groups, and has a porous structure with a three-dimensional network. When it is added to graphene oxide aerogel, the siloxane groups on the surface of fumed silica combine with the hydroxyl groups of graphene oxide hydrogel to prepare hybrid aerogel, which greatly improves the warmth retention effect of the fabric. The hybrid aerogel is combined with propylene trichlorosilane and grafted onto the macromolecular chain of polypropylene through maleic anhydride, which not only improves the compatibility of aerogel with polypropylene, but also solves the agglomeration problem of aerogel.

[0022] Secondly, the tourmaline is first calcined and then directly quenched and hydrated for modification, which not only increases the groups in the crystal that can generate infrared high-frequency vibrations, but also causes lattice distortion after the crystal is suddenly cooled, thereby enhancing the radiation of high-frequency short-wave infrared rays; the Si-OH groups on the surface of the tourmaline are combined with the active groups in the polyester molecular chain to be spun into hollow fibers; the graphene oxide and silicon dioxide in the aerogel can absorb the far-infrared emitted by the modified tourmaline to improve the utilization rate, and the aerogel that absorbs far-infrared can produce resonance effect and warm effect, penetrate into the deep layer of the skin, promote blood circulation, improve immune function, and achieve health care effects; the modified tourmaline has the ability to generate negative ions, and the addition of seagull stone powder can work together to achieve an antibacterial effect by destroying the structure of bacteria. The human body absorbs the far-infrared rays, negative ions, mineral elements, etc. released by tourmaline and negative ion powder, which promotes the skin to metabolize harmful substances, improve skin elasticity, and promote blood circulation and metabolism throughout the body, thereby achieving health care effects. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a thermal insulation and health care composite fabric prepared in the following examples are as follows:

[0025] Warmth retention: Test the warmth retention of sample fabrics according to GB / T11048-2008-T “Determination of thermal and moisture resistance of textiles under steady-state conditions of physiological comfort”.

[0026] Health care: far infrared performance test is carried out on sample fabrics.

[0027] Example 1

[0028] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1:1, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen at a quick freezing temperature of -40°C, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed aerogel;

[0029] (2) 8 parts of polypropylene, 0.5 parts of acryltrichlorosilane, 0.5 parts of maleic anhydride, 0.001 parts of benzoyl peroxide catalyst, and 0.4 parts of mixed aerogel were put into a high-speed stirrer, first stirred at a low speed of 60 rpm for 5 minutes, and then stirred at a high speed of 400 rpm for 15 minutes, and the stirring temperature was controlled to be 100°C to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature was 200°C, after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles were put into a spinning screw extruder, the screw extrusion temperature was set to 190°C, the molten material entered the spinneret with a hole number of 24 through the spinneret assembly to extrude into melt fibers, and then cooled by cooling air with a wind temperature of 30°C, and then stretched by a hot roller at 50°C, the stretching ratio was 1.5, and finally wound on a winder with a winding speed of 1500m / min to obtain modified polypropylene fibers;

[0030] (3) placing the tourmaline powder in a methane fluorine furnace, heating it to 500°C at a rate of 5°C / min, and continuing to calcine for more than 4 hours; quickly placing the calcined tourmaline powder in a magnesium hydroxide aqueous solution with a pH of 10 and a solid-liquid ratio of 1:5, soaking it for 1 hour, then filtering out the solid, repeatedly washing it with water until the filtrate is acid-base neutral, filtration, and aging it for 12 hours, and then drying it in a 60°C oven until the moisture content is less than 10%, thereby obtaining modified tourmaline powder;

[0031] (4) 6 parts of conventional polyester chips, 0.5 parts of modified tourmaline powder, 0.5 parts of 20 nm seagull stone powder, and 0.2 parts of ethyl acetate were put into a high-speed stirrer and stirred at a speed of 500 rpm for 30 minutes. The stirring temperature was controlled to be always at 220°C to make various raw materials evenly mixed. Then, the raw materials were put into a reactive twin-screw extruder with a screw extrusion temperature of 250°C. After melt mixing, the mixture was extruded, drawn, and pelletized to obtain polyester masterbatch; conventional polyester chips and polyester masterbatch were blended with a mass ratio of conventional polyester chips to polyester masterbatch of 1:1, and melt-spun at a spinning temperature of 290°C and a spinning speed of 2600 m / min, and a "C" type microporous spinneret was used to obtain modified polyester hollow fibers; modified polypropylene fibers and modified polyester hollow fibers were mixed and woven at a mass ratio of 1:0.5 to obtain a 150 g / m 2 Composite fabrics.

[0032] Example 2

[0033] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 3:1, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen at a quick freezing temperature of -40°C, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed aerogel;

[0034] (2) 8.8 parts of polypropylene, 1 part of acryltrichlorosilane, 1 part of maleic anhydride, 0.0015 parts of benzoyl peroxide catalyst, and 1.1 parts of mixed aerogel were put into a high-speed stirrer, first stirred at a low speed of 90 rpm for 10 minutes, and then stirred at a high speed of 600 rpm for 20 minutes, and the stirring temperature was controlled to be always at 100°C to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature was 215°C, after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles were put into a spinning screw extruder, the screw extrusion temperature was set to 220°C, the molten material entered the spinneret with a hole number of 24 through the spinneret assembly to extrude into melt fibers, and then cooled by cooling air with a wind temperature of 30°C, and then stretched by a hot roller at 70°C, the stretching ratio was 2.25, and finally wound on a winder with a winding speed of 2250m / min to obtain modified polypropylene fibers;

[0035] (3) placing the tourmaline powder in a muffle furnace, heating it to 600°C at a rate of 7.5°C / min, and continuing to calcine for more than 4 hours; quickly placing the calcined tourmaline powder in a magnesium hydroxide aqueous solution with a pH of 10 and a solid-liquid ratio of 1:12.5, soaking it for 2 hours, then filtering out the solid, repeatedly washing it with water until the filtrate is acid-base neutral, filtration, and aging it for 18 hours, and then drying it in a 60°C oven until the moisture content is less than 10%, thereby obtaining modified tourmaline powder;

[0036] (4) 7 parts of conventional polyester chips, 1 part of modified tourmaline powder, 0.75 parts of 20 nm seagull stone powder, and 0.45 parts of ethyl acetate were put into a high-speed stirrer and stirred at a speed of 500 rpm for 30 minutes. The stirring temperature was controlled to be always at 220°C to make various raw materials evenly mixed. Then, the raw materials were put into a reactive twin-screw extruder with a screw extrusion temperature of 260°C. After melt mixing, the mixture was extruded, drawn, and pelletized to obtain polyester masterbatch. Conventional polyester chips and polyester masterbatch were blended in a mass ratio of 1:1. The mixture was melt-spun at a spinning temperature of 290°C and a spinning speed of 2600 m / min. A "C" type microporous spinneret was used to obtain modified polyester hollow fibers. Modified polypropylene fibers and modified polyester hollow fibers were mixed and woven in a mass ratio of 1:1.25 to obtain a polyester fiber with a gram weight of 175 g / m2 Composite fabrics.

[0037] Example 3

[0038] (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 5:1, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen at a quick freezing temperature of -40°C, and then drying the frozen mixed dispersion in a vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare a mixed aerogel;

[0039] (2) 9.6 parts of polypropylene, 1.5 parts of propylene trichlorosilane, 1.5 parts of maleic anhydride, 0.002 parts of benzoyl peroxide catalyst, and 1.8 parts of mixed aerogel were put into a high-speed stirrer, first stirred at a low speed of 120 rpm for 15 minutes, and then stirred at a high speed of 800 rpm for 25 minutes, and the stirring temperature was controlled to be 100° C. to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature was 230° C., after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles were put into a spinning screw extruder, the screw extrusion temperature was set to 1250° C., the molten material entered the spinneret with a hole number of 24 through the spinneret assembly to extrude into melt fibers, and then cooled by cooling air with a wind temperature of 30° C., and then stretched by a hot roller at 90° C., the stretching ratio was 3.0, and finally wound on a winder with a winding speed of 3000 m / min to obtain modified polypropylene fibers;

[0040] (3) placing the tourmaline powder in a methane fluorine furnace, heating it to 700°C at a rate of 10°C / min, and continuing to calcine for more than 4 hours; quickly placing the calcined tourmaline powder in a magnesium hydroxide aqueous solution with a pH of 11 and a solid-liquid ratio of 1:20, soaking for 3 hours, then filtering out the solid, repeatedly washing with water until the filtrate is acid-base neutral, filtration, and aging for 24 hours, and then drying in a 60°C oven until the moisture content is less than 10%, thereby obtaining modified tourmaline powder;

[0041] (4) 9 parts of conventional polyester chips, 1.5 parts of modified tourmaline powder, 1 part of 20 nm seagull stone powder, and 0.7 parts of ethyl acetate were put into a high-speed stirrer and stirred at a speed of 500 rpm for 30 minutes. The stirring temperature was controlled to be always at 220°C to make various raw materials evenly mixed. Then, the raw materials were put into a reactive twin-screw extruder with a screw extrusion temperature of 270°C. After melt mixing, the mixture was extruded, drawn, and pelletized to obtain polyester masterbatch. Conventional polyester chips and polyester masterbatch were blended with a mass ratio of 1:1 to the polyester masterbatch. The mixture was melt-spun at a spinning temperature of 290°C and a spinning speed of 2600 m / min. A "C" type microporous spinneret was used to obtain modified polyester hollow fibers. Modified polypropylene fibers and modified polyester hollow fibers were mixed and woven at a mass ratio of 1:2 to obtain a 200 g / m 2 Composite fabrics.

[0042] Comparative Example 1

[0043] The difference between Comparative Example 1 and Example 2 lies in the difference in steps (1) (2). Steps (1) (2) are changed to: (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min, and then flash freezing the dispersion in liquid nitrogen at a quick freezing temperature of -40°C, and then drying the frozen dispersion in vacuum for 24 h at a vacuum degree of -0.085 MPa to prepare an aerogel;

[0044] (2) 8.8 parts of polypropylene, 1 part of acryltrichlorosilane, 1 part of maleic anhydride, 0.0015 parts of benzoyl peroxide catalyst, and 1.1 parts of aerogel were put into a high-speed stirrer, first stirred at a low speed of 90 rpm for 10 minutes, and then stirred at a high speed of 600 rpm for 20 minutes, and the stirring temperature was controlled to be always at 100° C. to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature was 215° C., after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles were put into a spinning screw extruder, the screw extrusion temperature was set to 220° C., the molten material entered the spinneret with a hole number of 24 through the spinneret assembly to extrude into melt fibers, and then cooled by cooling air with a wind temperature of 30° C., and then stretched by a hot roller at 70° C., the stretching ratio was 2.25, and finally wound on a winder with a winding speed of 2250 m / min to obtain modified polypropylene fibers; the remaining steps were the same as in Example 2.

[0045] Comparative Example 2

[0046] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: 8.8 parts of polypropylene, 1 part of maleic anhydride, 0.0015 parts of benzoyl peroxide catalyst, and 1.1 parts of mixed aerogel are put into a high-speed stirrer, first stirred at a low speed of 90 rpm for 10 minutes, and then stirred at a high speed of 600 rpm for 20 minutes, and the stirring temperature is controlled to be always at 100 ° C. to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature is 215 ° C, and the melt is After melt mixing, the mixture is extruded, drawn and pelletized to obtain blended particles; the blended particles are then put into a spinning screw extruder, the screw extrusion temperature is set to 220°C, the molten material enters a spinneret with 24 holes through a spinneret assembly and is extruded into melt fibers, and then cooled by cooling air at a temperature of 30°C, and then stretched by a hot roller at 70°C with a stretching multiple of 2.25, and finally wound on a winder at a winding speed of 2250m / min to obtain modified polypropylene fibers; the remaining steps are the same as those in Example 2.

[0047] Comparative Example 3

[0048] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: 8.8 parts of polypropylene, 1 part of acryltrichlorosilane, 0.0015 parts of benzoyl peroxide catalyst, and 1.1 parts of mixed aerogel are put into a high-speed stirrer, first stirred at a low speed of 90 rpm for 10 minutes, and then stirred at a high speed of 600 rpm for 20 minutes, and the stirring temperature is controlled to be always at 100 ° C. to make various raw materials evenly mixed, and then put into a reactive twin-screw extruder, and the screw extrusion temperature is 215 ° C. After melt mixing, the mixture is extruded, drawn and pelletized to obtain blended particles; the blended particles are then put into a spinning screw extruder, the screw extrusion temperature is set to 220° C., the molten material enters a spinneret with 24 holes through a spinneret assembly and is extruded into melt fibers, and then cooled by cooling air at a temperature of 30° C., and then stretched by a hot roller at 70° C. with a stretching multiple of 2.25, and finally wound on a winder at a winding speed of 2250 m / min to obtain modified polypropylene fibers; the remaining steps are the same as those in Example 2.

[0049] Comparative Example 4

[0050] The difference between Comparative Example 4 and Example 2 is that there is no step (1), and step (2) is changed to: 8.8 parts of polypropylene, 1 part of propenyl trichlorosilane, 1 part of maleic anhydride, 0.0015 parts of benzoyl peroxide catalyst, 0.55 parts of fumed silica, and 0.55 parts of graphene oxide are put into a high-speed stirrer, first stirred at a low speed of 90 rpm for 10 minutes, and then stirred at a high speed of 600 rpm for 20 minutes, and the stirring temperature is controlled to be always at 100 ° C. to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, and the screw extruder is The outlet temperature is 215°C. After melt mixing, the mixture is extruded, drawn and pelletized to obtain blended particles. The blended particles are then put into a spinning screw extruder, and the screw extrusion temperature is set to 220°C. The molten material enters a spinneret with 24 holes through a spinneret assembly and is extruded into melt fibers. The fibers are then cooled by cooling air at a temperature of 30°C, and then stretched by a hot roller at 70°C with a stretching multiple of 2.25. Finally, the fibers are wound on a winder at a winding speed of 2250m / min to obtain modified polypropylene fibers. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 5

[0052] The difference between Comparative Example 5 and Example 2 is that there is no step (3), and step (4) is changed to: 7 parts of conventional polyester chips, 1 part of tourmaline powder, 0.75 parts of 20nm seagull stone powder, and 0.45 parts of ethyl acetate are put into a high-speed stirrer, stirred at a speed of 500rpm for 30min, and the stirring temperature is controlled to be always at 220°C to make various raw materials evenly mixed, and then put into a reactive twin-screw extruder, the screw extrusion temperature is 260°C, after melt mixing, extrusion, drawing, and pelletizing to obtain polyester masterbatch; conventional polyester chips and polyester masterbatch are blended, the mass ratio of conventional polyester chips to polyester masterbatch is 1:1, melt spinning is carried out at a spinning temperature of 290°C and a spinning speed of 2600m / min, and a "C" type microporous spinneret is used to obtain modified polyester hollow fiber; modified polypropylene fiber and modified polyester hollow fiber are mixed and woven at a mass ratio of 1:1.25 to make a gram weight of 175g / m 2 The remaining steps are the same as those in Example 2.

[0053] Effect example

[0054] Table 1 below shows the performance analysis results of a thermal insulation and health care composite fabric using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0055] Table 1

[0056] Clo value (clo) Far infrared normal emissivity (%) Example 1 1.32 87.5 Example 2 1.34 87.6 Example 3 1.34 87.5 Comparative Example 1 1.23 84.5 Comparative Example 2 1.29 86.7 Comparative Example 3 1.28 86.4 Comparative Example 4 0.72 85.6 Comparative Example 5 1.30 72.1

[0057] From the comparison of the experimental data of the Crowe values ​​of the embodiment and the comparative example, it can be found that the present invention combines fumed silica with graphene oxide aerogel, and the siloxy groups on the surface of the fumed silica are combined with the hydroxyl groups of the graphene oxide hydrogel to prepare a hybrid aerogel, which greatly improves the warmth retention effect of the fabric; the hybrid aerogel is combined with acryltrichlorosilane and grafted onto the macromolecular chain of polypropylene through maleic anhydride, which not only improves the compatibility of the aerogel with polypropylene, but also solves the agglomeration problem of the aerogel. From the comparison of the experimental data of the far-infrared normal emissivity of the embodiment and the comparative example, it can be found that the present invention first calcines the tourmaline and then directly quenches and hydrates it, which not only increases the groups in the crystal that can generate infrared high-frequency vibrations, but also causes the lattice distortion after the crystal is suddenly cooled, so that the radiation of high-frequency short-wave infrared rays is enhanced; and the Si-OH groups on the surface of the tourmaline are combined with the active groups in the polyester molecular chain to be spun into hollow fibers; the graphene oxide and silicon dioxide in the aerogel can absorb the far-infrared emitted by the modified tourmaline, thereby improving the utilization rate; the aerogel that absorbs the far-infrared can also produce a resonance effect and a warming effect, penetrate into the deep layer of the skin, promote blood circulation, improve immune function, and achieve a health-care effect; the modified tourmaline has the ability to generate negative ions, and the addition of seagull stone powder works together to achieve an antibacterial effect by destroying the structure of bacteria. The human body absorbs the far-infrared rays, negative ions, mineral elements, etc. released by the tourmaline and the negative ion powder, which promotes the skin to metabolize harmful substances, improves skin elasticity, and promotes blood circulation and metabolism throughout the body, thereby achieving a health-care effect.

[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A thermal insulation and health care composite fabric, characterized in that: The fabric is formed by composite weaving of modified polypropylene fiber and modified polyester hollow fiber.

2. A thermal insulation and health care composite fabric according to claim 1, characterized in that: The modified polypropylene fiber is prepared by preparing a mixed aerogel of fumed silica and graphene, which is then combined with acryltrichlorosilane and spun by grafting maleic anhydride into polypropylene.

3. The thermal insulation and health care composite fabric according to claim 1, characterized in that: The modified polyester hollow fiber is prepared by spinning modified tourmaline powder, seagull stone powder and polyester.

4. A method for preparing a thermal insulation and health care composite fabric, characterized in that: The method comprises the following preparation steps: (1) adding dried graphite oxide to deionized water to form a dispersion with a concentration of 2.5 mg / mL, and then adding fumed silica, the molar ratio of graphene oxide to fumed silica being 1-5:1, stirring at 120 rpm for 20 min, and then ultrasonicating at 60 kHz for 20 min to prepare a mixed dispersion, and then flash freezing the mixed dispersion in liquid nitrogen, and then drying the frozen mixed dispersion in vacuum for 24 h, the vacuum degree being -0.085 MPa, to prepare a mixed aerogel; (2) 8-9.6 parts of polypropylene, 0.5-1.5 parts of allyltrichlorosilane, 0.5-1.5 parts of maleic anhydride, 0.001-0.002 parts of catalyst, and 0.4-1.8 parts of mixed aerogel are placed in a high-speed stirrer, first stirred at a low speed of 60-120 rpm for 5-15 minutes, then stirred at a high speed of 400-800 rpm for 15-25 minutes, and the stirring temperature is controlled to be always at 100° C. to make various raw materials evenly mixed, and then placed in a reactive twin-screw extruder for screw extrusion. The temperature is 200-230°C, after melt mixing, extrusion, drawing, and pelletizing to obtain blended particles; then the blended particles are put into a spinning screw extruder, and the molten material enters a spinneret with 24 holes through a spinneret assembly to be extruded into melt fibers, and then cooled by cooling wind with a wind temperature of 30°C, and then stretched by a hot roller at 50-90°C, with a stretching multiple of 1.5-3.0, and finally wound on a winder with a winding speed of 1500-3000m / min to obtain modified polypropylene fibers; (3) placing the tourmaline powder in a methane fluorine furnace, heating it to 500-700° C., and continuing to calcine for more than 4 hours; quickly placing the calcined tourmaline powder in a magnesium hydroxide aqueous solution with a pH of 10-11 and a solid-to-liquid ratio of 1:5-20, soaking for 1-3 hours, then filtering out the solid, repeatedly washing with water until the filtrate is acid-base neutral, filtration, and aging for 12-24 hours, and then drying in a 60° C. oven until the moisture content is less than 10%, thereby obtaining modified tourmaline powder; (4) 6-9 parts of conventional polyester chips, 0.5-1.5 parts of modified tourmaline powder, 0.5-1 parts of 20 nm seagull stone powder, and 0.2-0.7 parts of ethyl acetate are put into a high-speed stirrer, stirred at a speed of 500 rpm for 30 minutes, and the stirring temperature is controlled to be always at 220°C to make various raw materials uniformly mixed, and then put into a reactive twin-screw extruder, and the screw extrusion temperature is 250-270°C. After melt mixing, extrusion, drawing, and pelletizing, polyester masterbatch is obtained; conventional polyester chips and polyester masterbatch are blended, melt-spun at a spinning temperature of 290°C and a spinning speed of 2600m / min, and a "C" type microporous spinneret is used to obtain modified polyester hollow fibers; modified polypropylene fibers and modified polyester hollow fibers are mixed and woven at a mass ratio of 1:0.5-2 to prepare composite fabrics.

5. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: The quick freezing temperature in step (1) is -40°C.

6. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: The catalyst in step (2) is benzoyl peroxide.

7. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: In the step (2), the screw extrusion temperature is 190-250°C.

8. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: The heating rate in step (3) is 5-10°C / min.

9. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: In the step (4), the mass ratio of conventional polyester chips to polyester masterbatch is 1:

1.

10. The method for preparing a thermal insulation and health-care composite fabric according to claim 4, characterized in that: The fabric weight in step (4) is 150-200 g / m 2 .

Citation Information

Patent Citations

  • Preparation method of heat-preserving comfortable modified polyester composite fiber

    CN104328553A

  • Preparation method of graphene / silica composite particles

    CN107325328A

  • Environment-friendly thermal insulation material and preparation method thereof

    CN111943713A

  • Far-infrared negative ion functional fiber as well as preparation method and application thereof

    CN112779624A

  • Preparation method of cashmere-like double-hollow polyester blanket

    CN113389057A